Kinematics and Tracking Control of a Four Axis Antenna for Satcom on the Move - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, we propose a 4 axis antenna which is capable of tracking satellites, through the precise real-time control of azimuth, cross-level, elevation and polarization angles. Due to the well-known gimbal lock problem in 2-3 axis antenna systems, our design has a redundant degree of freedom, and this redundancy is utilised to solve the issue of inverse kinematics around singularities. In the paper, we derive the kinematics of the 4 DOF redundant orientation mechanism and propose a method to avoid the gimbal lock issue. Also, utilising satellite position data (from TLE Database) and GPS localisation, we derive the necessary kinematics equations to position the antenna towards any visible satellite from any position on earth. Furthermore, we propose a PI-based cascade controller for tracking the satellites. To verify our analytical results we present experimental results on a 4 axis antenna test platform that we have built and compare our results with the feedback from a satellite in the form of guidance RF signals. The proposed system can find and track satellites with a 1-degree error without satellite signal feedback. © 2018 IEEJ Industry Application Society.
Keywords: Kinematics Equation; Redundant Robot; Servo Control; SOTM Antenna